Lost in Translation? Bill 21, International Human Rights, and the Margin of Appreciation - Mégret, Frédéric (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2020)
The adoption of Bill 21, which bans religious symbols for civil servants in Quebec, has stirred considerable debate politically and constitutionally in the province and in the rest of Canada. Neglected, however, has been a more in-depth analysis of how international human rights law often serves as an implicit frame of reference for many of the debates surrounding Bill 21. This essay focuses, in particular, on the invocation of the case law of the European Court of Human Rights, which seems to have validated bans of religious symbols in various contexts. It gives an overview of that jurisprudence and specifies the parameters within which it operates, emphasizing the complexity of translating a supranational case law into a domestic debate. It argues that whilst Quebec is less alone in banning religious symbols than is sometimes argued, the European case law needs to be handled carefully. In particular, the essay emphasizes the importance of the so-called “margin of appreciation” as heavily impacting the outcome in those cases. Although the margin suggests that there is national leeway in adopting bans based on certain national traditions and specificities, it hardly opens the door to all bans. Rather, the margin emphasizes the significance of divergences between states parties on an issue and respect for procedural safeguards. The essay concludes with some thoughts on how importing human rights arguments out of context can be perilous, but also about how the margin itself may be problematic.